Use of poly(o-toluidine)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel - Chaudhari, Sudeshna; Patil, P. P.; Mandale, A. B.; Patil, K. R.; Sainkar, S. R. (Journal of Applied Polymer Science, 2007)
This study explored the possibility of using poly(o-toluidine) (POT)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel in a chloride environment. POT/ZrO2 nanocomposite coatings were synthesized on steel substrates through an electrochemical route. These coatings were characterized with cyclic voltammetry, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray photoelectron spectroscopy. The performance of POT/ZrO2 nanocomposites as protective coatings against the corrosion of mild steel in aqueous 3 wt % NaCl was evaluated with the potentiodynamic polarization technique and electrochemical impedance spectroscopy. The results of this study demonstrate that POT/ZrO2 nanocomposite coatings provide better protection for mild steel against corrosion than pure POT coatings. The corrosion potential was about 0.312 V versus a saturated calomel electrode, more positive in aqueous 3 wt % NaCl for the nanocomposite-coated steel than the uncoated steel, and the corrosion rate of steel was reduced by a factor of almost 51. (c) 2007 Wiley Periodicals, Inc.
Keywords: Coatings; conjugated polymers; FTIR; Nanocomposites; synthesis

Control of molecular aggregation in symmetrically substituted pi-conjugated bulky poly(p-phenylenevinylene)s and their copolymers - Resmi, R.; Amrutha, S. R.; Jayakannan, M. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
A new series of symmetrically substituted bulky PPV-copolymers based on poly(bis-2,5-(2-ethylhexyloxy)-1,4-phenylenevinylene) (BEH-PPV) bearing tricyclodecane (TCD) pendants were synthesized to study the effect of chain aggregation in the pi-conjugated polymer backbone. The composition of the copolymers was varied up to 100 mol % and the structures of the copolymer were confirmed by NMR and FTIR. The molecular weights of the copolymers were obtained as M(w) = 11,500-1,78,800 depending on the TCD-incorporation in BEH-PPV. The origin of the pi-aggregation was investigated using mixture of solvents (polar or nonpolar) or temperature as external stimuli. Absorption, photoluminescence, and time-resolved fluorescence decay techniques were employed as tools to trace molecular aggregation in solution and solid state. The TCD-substituted bulky copolymers showed almost twice the enhancement in photoluminescence compared with that of BEH-PPV Solvent-induced aggregation studies of copolymers revealed the existence of strong molecular aggregation in BEH-PPV compared with that of bulky copolymers. Variable temperature studies further evidence for the reversibility of molecular aggregation on beating/cooling cycles and showed isosbetic points with respect to free and aggregated polymer chains. Time-resolved fluorescent studies confirmed the existence of free and aggregated pi-conjugated species with a life time of 0.1 to 1.0 ns. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 2631-2646, 2009
Keywords: conjugated polymers; fluorescence; poly(p-phenylenevinylene); solution properties; Structure-property relationship

Synthesis, spectroscopy, and electrochemical investigation of new conjugated polymers containing thiophene and 1,3,4-thiadiazole in the main chain - Patil, Prashant S.; Haram, Nanda S.; Pal, Ravindra R.; Periasamy, N.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2012)
Novel photoluminescent donoracceptor poly(p-phenylenevinylene)-type conjugated polymers containing thiophene and 1,3,4-thiadiazole units in the main chain were synthesized from 2,5-bis(5-bromomethyl-2-thienyl)-1,3,4-thiadiazole and 1,3/1,4-benzenedialdehyde by WittigHorner reaction. The synthesized polymers were characterized by the use of thermal analysis and spectroscopic (infrared, UV-visible absorption, and photoluminescence) measurement. The resultant material exhibited bluish green, green, and orange fluorescence in their solution and thin film and solid forms, respectively. The redox property of the polymers has also been studied by cyclic voltammetry. The optical and electrochemical studies reveal that these novel polymers are new promising materials for the development of efficient polymer light-emitting diodes. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: conjugated polymers; photoluminescence; thiophene and thiadiazole-containing polymer

Facile one-pot reactive solution blending approach for main-chain donor-acceptor polymeric materials - Nisha, S. Kumari; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2013)
A high-temperature solution blending process has been used to synthesize a series of copolymers incorporating varying mole ratios of perylenebisimide (PBI) into the backbone of an engineering thermoplastic polyester [poly(1,4-cyclohexylenedimethylene-1,4-cyclohexanedicarboxylate)] (PCCD). A random donor-acceptor copolymer incorporating oligo(p-phenylene vinylene) (OPV) and PBI was also synthesized. The chemical incorporation of these chromophores into PCCD was confirmed by carrying out the melt condensation using 1,4-cyclohexanedimethanol and 1,4-dimethylcyclohexane dicarboxylate with hydroxyl-functionalized PBI and OPV derivatives. Higher extent of incorporation of PBI (35 mol %) could be achieved using the blending approach retaining solubility, film-forming ability, and higher molecular weights. The PBI polymers produced using the two different approaches exhibited structural variations. The polymers formed from the solution blending approach had a semicrystalline nature with blocks of PCCD separating the PBI units, whereas those produced using the melt condensation route were amorphous polymers. This structural variation was reflected in their photophysical properties also with the reactive solution-blended polymers exhibiting higher fluorescence quantum yields. These results demonstrate the easy incorporation of suitably functionalized donor and acceptor moieties into a completely aliphatic polyester backbone to produce free-standing films of hitherto nonprocessable polymers. (C) 2012 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 509-524
Keywords: blending; conjugated polymers; fluorescence; PCCD; Perylenebisimide; reactive blending; transesterification

Synthesis of amphiphilic isoindigo co-polymers for organic field effect transistors: A comparative study - Dharmapurikar, Satej S.; Arulkashmir, Arulraj; Mahale, Rajashree Y.; Chini, Mrinmoy Kumar (Journal of the apllied polymer science, 2017)
In this work, the amphiphilic isoindigo (am-iInd) based conjugated polymers namely poly(am-iInd-DT) and poly(am-iInd-TT) and their regular counterpart poly(reg-iInd-DT) and poly(reg-iInd-TT) were synthesized to compare their opto-electronic and charge transport properties. They were used to fabricate organic field effect transistors. Charge transport properties in conjugated polymers depend upon intermolecular interaction which is strongly affected by the nature of side chains. The amphiphilic nature of the conjugated polymers has little impact on the charge transport properties. The charge carrier mobility of amphiphilic conjugated polymers was comparable with the regular polymers except poly(reg-iInd-DT) which can be correlated by X-ray diffraction and thin film morphology. (c) 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 45461.
Keywords: Alkyl; Applications; Conducting polymers; Copolymers; Optical and Photovoltaic applications; conjugated polymers; High-performance; mobility; Packaging; Semicondoctors; Side-chains; Solar-cells; Thin-film Transformer